PENGARUH KEPRIBADIAN TERHADAP KETERIKATAN KARIR YANG DIMEDIASI OLEH ADAPTABILITAS KARIR - Alexandria Jamilatul Qadri, Murkhana (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2018)
Abstract:This study aims to determine the effect of personality to career enggagement with career adaptability as a mediating. The emprical study conducted at student of Syiah Kuala University used a questionaire as a research instrument, which samples in this study of 155 respondent. Probability Sampling is used as a sampling technique with Proportionate Random Sampling. Methods HLM (Hierarchical Linear Modelling) is used as a method of data analysis using software IBM SPSS 20. These result indicate that the personality positive and significant impact on creer enggagement, personality significantly and positively related to career adaptability, career adaptability have a positive and significant effect on career enggagement and in addition showed that the career adaptability mediate effect on personality to career enggagement.Keywords : Personality, Career Adaptability and Career Enggagement